1998
DOI: 10.1046/j.1365-2435.1998.00209.x
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthesis and respiration rates depend on leaf and root morphology and nitrogen concentration in nine boreal tree species differing in relative growth rate

Abstract: 1. To test several hypotheses about acclimation and adaptation of photosynthesis and respiration to differing light conditions, we investigated the interspecific relationships between leaf and root metabolism, chemistry and morphology in high and low light conditions for young seedlings of nine boreal tree species that differ in relative growth rate (RGR). 2. Light‐saturated net photosynthesis (Asat), whole‐plant nitrogen (N) uptake rates, leaf and root respiration and morphology, and RGR all varied in parall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

46
396
3
9

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 467 publications
(471 citation statements)
references
References 34 publications
46
396
3
9
Order By: Relevance
“…For example, Reich et al (1998) found root respiration and N uptake to be highly correlated with SRL among nine boreal tree species (Fig. 3).…”
Section: Parallels Between Roots and Leavesmentioning
confidence: 94%
“…For example, Reich et al (1998) found root respiration and N uptake to be highly correlated with SRL among nine boreal tree species (Fig. 3).…”
Section: Parallels Between Roots and Leavesmentioning
confidence: 94%
“…Despite soil environmental conditions created by irrigation and fertilization treatments, cottonwood genotypes produced roots Discussion with consistently higher SRL (narrower diameter) and greater root length densities as expected h m fast Ranking among genotypes in root system charactergrowing species originating from resource rich bottomistics were unaffected by resource availability and not land or alluvial sites (Comas and Eissenstat 2004; for the complete model with all parameters Genotypes were analyzed separately for Reich et al 1998), however, since sycamore is also a bottomland species, it too was expected to share these characteristics with cottonwood and to be unique from sweetgum, a more stress tolerant species with robust site requirements. Yet SRL values of sycamore and sweetgum were equivalent and distinct from that of cottonwood.…”
Section: Aboveground Growthmentioning
confidence: 97%
“…Broadleaved deciduous species are distinct from needle-leaved evergreen species (Comas and Eissenstat 2004;Einsmann et al 1999), yet other functional categories may also influence root characteristics. Stress tolerant tree species such as those living on upland well drained soils or those with robust site requirements are expected to have roots with larger diameters lower specific root length (SRL), lower specific respiration rates (Comas and Eissenstat 2004;Reich et al 1998) and lower turnover rates (Chapin 1980). They are also expected to be less responsive to heterogeneous resource availability (Einsmann et al 1999;Mou et al 1995) and have greater dependence on symbiotic mycorrhizal associations (Harley and Smith 1983).…”
Section: Introductionmentioning
confidence: 99%
“…The values for shade plants are lower because respiration rates are very low, therefore small assimilation rates are sufficient to bring the rates of CO 2 evolution to zero. Low respiratory rates seem to represent a basic adaptation that allows shade plants to survive in light-limited environments, since it is of utmost importance to minimise carbon losses via respiration in order to maintain a positive net carbon balance in highly shaded environments (Givnish, 1988;Reich et al 1998;Pearcy, 1998). Both species showed greater values of dark respiration (Rd) in the high light compared to the low light (p < 0.05), being significantly higher in G. ulmifolia than in H. courbaril only in high light (Table 1).…”
Section: Chlorophyll Contentmentioning
confidence: 99%